UPAYA MENINGKATKAN KOGNITIF SISWA DENGAN PENGGUNAAN MEDIA KINCIR ANGKA DI SD NEGERI 173655 LUMBAN RANG - Cornelia, Tina Sheba; Fahira, Zira; Rahmadini, Viralya (Jurnal Curere, 2024)
This research aims to improve students' cognitive abilities in recognizing number symbols through the use of number wheel media at SD Negeri 173655 Lumban Rang. This research used a qualitative approach with 18 students as subjects. The results of observations before the action showed that there were still few students who had the ability to recognize number symbols. By using number wheel media, this research shows an increase in students' cognitive abilities in recognizing number symbols and improves the learning atmosphere to be more enjoyable. The results of this research show that the number wheel media can improve students' cognitive abilities and foster students' enthusiasm for learning mathematics.